Efficacy of Transversus Abdominis Plane Block in Patients After Laparoscopic Radical Cervical Cancer Surgery - Ma, Xiaoyu; Gao, Yi; Wang, Jing; Wu, Zhen; Shen, Huasu; Wang, Ping (Frontiers in Surgery, 2022)
Objective To evaluate the efficacy of transversus abdominis plane block (TAPB) in patients after laparoscopic radical cervical cancer surgery. Methods A total of 120 patients with cervical cancer who underwent laparoscopic radical resection in the hospital from January 2019 to January 2020 were selected and concurrently assigned to either patient-controlled intravenous analgesia (PCIA) (Control group) or PCIA plus TAPB (Observation group) according to different methods. The Visual Analogue Scale (VAS), Bruggemann comfort scale (BCS), immune function indicators, hemodynamics, analgesia indicators, and postoperative recovery time were recorded and compared. Results Observation group had a lower VAS score and a higher BCS postoperatively versus Control group, and the difference were statistically significant. After operation, immune function indexes of patients in two groups were declined, and the difference was statistically significant. At 76h after operation, the immune function indexes of Control group were lower than Observation group , and the difference was statistically significant. After operation, Control group obtained a higher mean arterial pressure (MAP) at extubation, and the difference was statistically significant.Observation group outperformed Control group in terms of analgesia indicators and postoperative recovery time, and the difference were statistically significant. Conclusion TAPB can enhance the analgesic effect of patients after laparoscopic radical resection of cervical cancer, stabilize their physical signs, has little effect on the patient's immune function, with high safety profile.